Intergenerational transmission of disability stigma: the mediating role of family communication patterns and the moderating effect of cognitive empathy - Xiaoqi Cai; Lan Pan; Tao Wang (BMC Public Health)
Abstract Objective The objective of this study was to investigate the intergenerational transmission effect of parental stigma toward disability on children’s stigma toward disability. Additionally, the study aimed to explore the mediating role of family communication patterns and the moderating role of children’s cognitive empathy in this process. Methods A cross-sectional survey was conducted in 2024 with 1,106 students from fourth to ninth grade and their parents to examine the intergenerational transmission of stigma toward disability. Structural equation models were constructed using Mplus 8.0 software to explore the mediating effects of family communication patterns, and the moderating role of children’s cognitive empathy. Results The results indicated that parental disability stigma was positively correlated with children’s disability stigma and conformity-oriented family communication patterns. In contrast, conversation-oriented family communication was negatively correlated with parental disability stigma, children’s disability stigma, and conformity-oriented family communication. Children’s cognitive empathy was negatively correlated with children’s disability stigma. Family communication patterns, including both conversation orientation and conformity orientation, partially mediated the transmission of disability stigma from parents to children. Additionally, children’s cognitive empathy significantly moderated the mediating effect of conversation-oriented family communication on the intergenerational transmission of disability stigma. Conclusions The study highlights the role of family dynamics in the transmission of stigma toward individuals with disabilities across generations. Specifically, family communication patterns act as a mediator in the process, and children’s cognitive empathy moderates the effect of communication styles. These findings suggest that interventions aimed at reducing disability stigma should consider both family communication patterns and the development of children’s cognitive empathy.